Monopolistic Competition in a Large Economy with Differentiated Commodities - Hart, Oliver D. (Review of Economic Studies, 1979)
Journal Article Monopolistic Competition in a Large Economy with Differentiated Commodities Get access Oliver D. Hart Oliver D. Hart Churchill College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 1, January 1979, Pages 1–30, https://doi.org/10.2307/2297169 Published: 01 January 1979 Article history Received: 01 February 1977 Accepted: 01 December 1977 Published: 01 January 1979